2016
DOI: 10.1007/978-3-319-54660-5_24
|View full text |Cite
|
Sign up to set email alerts
|

Automatic Assembly Design for Engineering-to-Order Products Based on Multiple Models and Assembly Features

Abstract: When it comes to Engineering-To-Order (ETO) products, neither the exact number nor the form of the components in them can be predefined. Thus, existing assembly models and generative design techniques are not adequate to support development of design automation tools for ETO products. ETO companies usually use custom libraries with past case designs that are adjusted to a customer's requirements. This method is not cost effective and it is prone to human errors. In this work, we present the Automatic Assembly … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(4 citation statements)
references
References 33 publications
0
4
0
Order By: Relevance
“…At first, the assembly features were defined as high-level interfaces representing the relationships between components (Sodhi and Turner 1991;Chan and Tan 2003;Ahmad 2017;Neb 2019) implying engineering functions (Kang and Nnaji 1993), but shortly, their existence was linked to the form features on the separate parts that make up the assembly (geometrical information) (Shah and Rogers 1993;Deneux 1999;Whitney et al 1999;Qiao and Zhu 2011;Xu et al 2014;Vemulapalli et al 2014;Chatziparasidis and Sapidis 2016). Zha and Du (2002) reported that keeping the conditions of assembled parts related to the part's form features present advantages such as facilitating design for assembly and process planning, easy extraction of fit and tolerances for analysis, and providing direct feedback to the designers on the troublesome form features based on the assembly evaluation.…”
Section: Assembly Feature Definitionmentioning
confidence: 99%
See 1 more Smart Citation
“…At first, the assembly features were defined as high-level interfaces representing the relationships between components (Sodhi and Turner 1991;Chan and Tan 2003;Ahmad 2017;Neb 2019) implying engineering functions (Kang and Nnaji 1993), but shortly, their existence was linked to the form features on the separate parts that make up the assembly (geometrical information) (Shah and Rogers 1993;Deneux 1999;Whitney et al 1999;Qiao and Zhu 2011;Xu et al 2014;Vemulapalli et al 2014;Chatziparasidis and Sapidis 2016). Zha and Du (2002) reported that keeping the conditions of assembled parts related to the part's form features present advantages such as facilitating design for assembly and process planning, easy extraction of fit and tolerances for analysis, and providing direct feedback to the designers on the troublesome form features based on the assembly evaluation.…”
Section: Assembly Feature Definitionmentioning
confidence: 99%
“…Later, the assembly process representation by Qiao and Zhu (2011) used three assembly features categories: structure features, whose information assisted the planner in defining the assembly sequence and cell design; fix features, which aided in the fixturing, clamping, and transportation planning; and, operation feature, which contained the information about the connection itself. Finally, Chatziparasidis and Sapidis (2016) proposed a classification based on the geometrical entities connecting the parts. Form assembly features, depending on existing form features; skeleton assembly features, using basic auxiliary entities such as planes and axes; and composite assembly features, employing complementary geometrical entities to complete the geometric description, were used in an automatic assembly synthesis model.…”
Section: Assembly Feature Classificationmentioning
confidence: 99%
“…47. Triaxial accelerometers are placed again at six (6) selected locations. The two locations where the safety gears are mounted along with four other locations which are used as reference locations.…”
Section: Analysis Of the Complete Elevator Systemmentioning
confidence: 99%
“…SEVaM uses experimental results as input in the simulation models and contains procedures allowing the simulation model to be calibrated to given experimental results. The product configuration from the KBE system is then passed to a custom developed CAD application, based on the Automatic Assembly Synthesis Model (AASM) and Assembly Features [6,7], that automatically generates all the 3D CAD components and synthesizes the final 3D CAD assembly model.…”
Section: Introductionmentioning
confidence: 99%